2015
DOI: 10.2527/jas.2015-9149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet form and type on growth performance, carcass yield, and iodine value of finishing pigs1

Abstract: Two experiments were conducted to determine the effects of pelleting, diet type (fat and fiber level), and withdrawal of dietary fiber and fat before marketing on growth performance, carcass yield, and carcass fat iodine value (IV) of finishing pigs. Each experiment used 288 pigs (initially 49.6 and 48.5 kg BW, respectively) with 6 dietary treatments arranged as 2 × 3 factorials. In Exp. 1, main effects were diet form (meal vs. pellet) and diet regimen. Diet regimens were 1) a low-fiber, low-fat (corn-soybean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…1 and 2, IV increased by approximately 2–3 units, which could become meaningful if pigs are marketed to processing facilities that have quality control standards for carcass fat IV. Nevertheless, this response in belly fat IV is consistent with other literature where increased DDGS withdrawal period prior to harvest decreased IV ( Benz et al, 2008 ; Asmus et al, 2014 ; Nemechek et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…1 and 2, IV increased by approximately 2–3 units, which could become meaningful if pigs are marketed to processing facilities that have quality control standards for carcass fat IV. Nevertheless, this response in belly fat IV is consistent with other literature where increased DDGS withdrawal period prior to harvest decreased IV ( Benz et al, 2008 ; Asmus et al, 2014 ; Nemechek et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
“… Coble et al (2017) fed 0% or 30% DDGS for 20 d prior to market and observed no final BW effects, but feeding DDGS decreased HCW and yield. This response is consistent with much of the literature evaluating removing DDGS from the diet before harvest ( Gaines et al, 2007a ; Nemechek et al, 2015 ). Though the impact of feeding DDGS on carcass yield is well understood, the suggested time to remove DDGS from diets to restore yield varies.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations